Nasyid competition assessment using fuzzy evaluation method / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Mohd Idris, Mohd Fazril Izhar; Wan Daud, Wan Suhana; Yaacob, Muhammad Yazwan Aiman (UiTM Cawangan Perlis, 2023)
The nasyid competition evaluates a participant's performance based on several factors, including Voice, Music, Lyrics, and Performance. Participants in the nasyid competition are usually assigned a point value of 100, with each point representing a linguistic word such as “Perfect”, “Spectacular”, “Very Good” and so on. Evaluating participant performance is especially difficult because it involves human decision-making, which is imprecise, ambiguous, and unpredictable. This study employs the fuzzy evaluation method to assess participant performance at a nasyid competition held in Kedah. In this manner, the membership function graph was used to determine the membership value of each satisfaction level. When fuzzy numbers are used, the fuzzy markings are created more consistently. The satisfaction level of each participant’s mark would then be computed. In the end, the fuzzy markings with linguistic value would be obtained. The proposed assessment method has a bright future in evaluating those participants’ performance because it provides an alternative approach to assessing performance.